Physiological and anthropometric characteristics of junior cyclists of different specialties and performance levels - Menaspa, P.; Rampinini, E.; Bosio, A.; Carlomagno, D.; Riggio, M.; Sassi, A. (Scandinavian Journal of Medicine & Science in Sports, 2012)
This study analyzes the anthropometric and physiological characteristics of junior cyclists within different cycling specialties and different performance levels. One hundred and thirty-two junior riders (16.8 ± 0.6 years, 177 ± 6 cm, 66.3 ± 6.7 kg) were tested for anthropometric, aerobic and anaerobic parameters. Cyclists were classified within specialties [uphill (UH) flat terrain (FT) all terrain (AT) and sprint (SP)] and performance levels, based on a seasonal ranking [low level (LL) medium level (ML) and high level (HL)]. The results of the two-way analysis of variance showed that FT and SP have greater body dimensions than UH and AT (P<0.001). Concerning the relative aerobic parameters, AT and UH have higher values (P<0.001) than FT and SP [maximal oxygen uptake (VO2max): 69.4 ± 3.6, 67.5 ± 5.0, 62.8 ± 4.5 and 61.9 ± 4.1 mL/kg/min, respectively] while absolute parameters resulted higher for FT and AT (P?0.008). The relative power produced in the 5 s test was higher (P<0.001) for AT and SP than FT and UH (16.7 ± 1.1, 16.6 ± 0.6, 14.9 ± 1.7 and 14.4 ± 1.7 W/kg, respectively). Concerning the performance level, only the age and the aerobic parameters resulted differently within levels (VO2max: HL=67.3 ± 4.9, ML=65.5 ± 5.1 and LL=63.3 ± 5.2 mL/kg/min), with the highest values for HL (P</=0.007). In conclusion, juniors are specialized in the same way as professional cyclists and the aerobic characteristics are confirmed as significant in the performance level assessment.